NILAI KEISLAMAN DAN KEARIFAN LOKAL DALAM PENGEMBANGAN PARIWISATA HALAL PASCA COVID 19 DI KOTA MALANG - Budiyono Santoso (Pustaka Peradaban, 2022)
Cultural and religious values have great potential in the development of halal tourism. Religious values and local wisdom can play a role both in destination development and in tourist services. The city of Malang as one of the pilots of the halal tourism city project, can take advantage of Islamic values and local wisdom that exists in the community to develop halal tourism. This article seeks to explore Islamic values and local wisdom of the people of Malang City and their implementation in the development of halal tourism. This study proposes prophetic traits (shiddiq, amanah, tabligh, fathonah) as Islamic values to be used in the development of halal tourism in Malang City. Meanwhile, diversity, progressiveness and egalitarianism are values of local wisdom that support the development of Halal tourism in Malang City. The prophetic nature in the development of halal tourism in Malang is implemented, one of which is the commitment to meet the standard of the halal assurance system, Clean, Health, Safety, and Environmental Sustainability (CHSE) certification, attention to environmental sustainability, community empowerment and the development of promotional innovations with information technology and social media. While the “arek” culture in Malang City with the characteristics of diversity, open to change, adaptable, egalitarian and progressive is implemented in the development of thematic villages and the active role of the community in the development of tourist destinations in Malang City. Nilai-nilai budaya dan agama mempunyai potensi besar dalam pengembagan wisata halal. Nilai agama dan kearifan lokal dapat berperan baik dalam pembangunan destinasi maupun dalam pelayanan wisatawan. Kota Malang sebagai salah satu pilot Proyek kota wisata halal, dapat memanfaatkan nilai-nilai Islam dan kearifan lokal yang ada dalam masyarakat untuk mengembangkan pariwisata halal. Artikel ini berupaya menggali nilai-nilai Islami dan kearifan lokal masyarakat Kota Malang serta implementasinya dalam pembangunan pariwisata halal. Kajian ini mengusulkan sifat kenabian (shiddiq, amanah, tabligh, fathonah) sebagai nilai Islami untuk digunakan dalam pengemabangan pariwisata halal di Kota Malang. Sedangkan keragaman, progresifitas dan egalitarianisme menjadi nilai kekearifan lokal yang mendukung pengembangan pariwisata Halal di Kota Malang. Sifat kenabian dalam pembangunan pariwisata halal di Kota Malang diimplementasikan salah satunya dalam komitmen untuk memenuhi standard system jaminan halal, sertifikasi Clean, Health, Safety, and Enviroment Sustainability (CHSE), perhatian kepada kelestarian lingkungan, pemberdayaan masyarakat dan pengembangan inovasi promosi dengan teknologi informasi dan media sosial. Sedangkan kebudayaan “arek” di Kota Malang dengan ciri khas keragaman, terbuka terhadap perubahan, mudah beradaptasi, egaliter dan Progresif di implementasikan dalam pengembangan kampung tematik dan peran aktif masyarakat dalam pembangunan destinasi wisata di Kota Malang.